2004
DOI: 10.1207/s15327604jaws0703_1
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Primiparous Maternal and Infant Gorilla(Gorilla gorilla gorilla)Behavior

Abstract: A primiparous mother and her infant were subjects of a longitudinal behavioral study at Lincoln Park Zoo in Chicago, Illinois. From November 1998 to November 1999, we collected a total of 100 hr of focal nonhuman animal instantaneous point sampling and all occurrence data on the mother and her infant. After 8 months, we introduced the 4-member focal group to an 8-member gorilla group, thus providing an opportunity to study the effect of the introduction on mother-infant behavior. Overall, time the pair spent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Only Ai changed her behavior toward Oki during the course of this study. The social environment has been reported to affect the early development of gorilla infants in groups that consisted of more individuals than the group in this study (Crosby & Lukas, 2004;Maple & Warren-Leubecker, 1983;Meder, 1989;Meder, 1990;Nakamichi, Silldorff, Bringham, & Sexton, 2004). As in those studies, Ai's demand for contact with her mother might have decreased, while her demand for other environmental factors, including the nonkin female, might have increased from the age of 7 months to 19 months in the group studied here.…”
Section: Discussionmentioning
confidence: 43%
“…Only Ai changed her behavior toward Oki during the course of this study. The social environment has been reported to affect the early development of gorilla infants in groups that consisted of more individuals than the group in this study (Crosby & Lukas, 2004;Maple & Warren-Leubecker, 1983;Meder, 1989;Meder, 1990;Nakamichi, Silldorff, Bringham, & Sexton, 2004). As in those studies, Ai's demand for contact with her mother might have decreased, while her demand for other environmental factors, including the nonkin female, might have increased from the age of 7 months to 19 months in the group studied here.…”
Section: Discussionmentioning
confidence: 43%
“…Since gorillas have long life spans and few offspring, datasets with large samples sizes and high enough mortality to analyze are rare. Much of what is known about motheroffspring interactions comes from case studies of individual pairs or a few gorillas in one location [Crosby & Lukas, 2004;Maestripieri et al, 2002;Stokes et al, 2003]. The international studbook for the western lowland gorilla [Wilms, 2011] provides a large dataset for analyzing variables that influence early life mortality, potentially producing valuable insights regarding survival and reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the responsive care chim panzees w ere m ore persistent in attaining goals, had longer attention spans, and exhibited higher levels o f cooperation than the chim panzees in the two standard care groups (Bard & Gardner, 1996). In a case study exam ining a m other-infant gorilla dyad, Crosby and Lukas (2004) found that the m other's care w as adequate, but not as robust as care dem onstrated by other gorilla mothers. F or exam ple, direct physical contact occurred infrequently and the mother rarely approached the infant, despite repeated attem pts by the infant to initiate contact.…”
Section: Attachment Theory: An Overviewmentioning
confidence: 97%
“…The authors concluded that despite this m inim al level o f care, the infant w as not detrim entally affected. Specifically, Crosby and Lukas (2004) found that the infant did not…”
Section: Attachment Theory: An Overviewmentioning
confidence: 99%